2009
DOI: 10.1073/pnas.0900896106
|View full text |Cite
|
Sign up to set email alerts
|

Model of mouth-to-mouth transfer of bacterial lipoproteins through inner membrane LolC, periplasmic LolA, and outer membrane LolB

Abstract: Outer membrane-specific lipoproteins in Escherichia coli are released from the inner membrane by an ATP-binding cassette transporter, the LolCDE complex, which causes the formation of a soluble complex with a periplasmic molecular chaperone, LolA. LolA then transports lipoproteins to the outer membrane where an outer membrane receptor, LolB, incorporates lipoproteins into the outer membrane. The molecular mechanisms underlying the Loldependent lipoprotein sorting have been clarified in detail. However, it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
110
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 27 publications
6
110
1
Order By: Relevance
“…The photo-cross-linking experiments suggested that some residues that were identified by the preset study exhibited the high efficiency of the cross-linking (28). Therefore, these observations also support the interaction mode.…”
Section: Discussionsupporting
confidence: 56%
“…The photo-cross-linking experiments suggested that some residues that were identified by the preset study exhibited the high efficiency of the cross-linking (28). Therefore, these observations also support the interaction mode.…”
Section: Discussionsupporting
confidence: 56%
“…The cavity is covered by a lid comprising short ␣ helices. The inside of the cavity is hydrophobic and binds to the acyl chains of lipoproteins (30). To study the importance of the opening and closing of the lid covering the cavity, we constructed a LolA mutant protein having two mutations, I93C and F140C (43).…”
mentioning
confidence: 99%
“…Membrane localization of LolA(I93C/F140C). It was shown recently by means of in vivo photo-cross-linking that the region around the entrance of the hydrophobic cavity of LolA physically interacts with LolC (20). It therefore seemed likely that the toxic effect of I93C/F140C is suppressed by the formation of the I93C/F140C-LolCDE complex.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these results indicate that the oxidized form of I93C/F140C more strongly binds to LolCDE. It was recently found by means of an in vivo photo-cross-linking technique that LolA specifically interacts with LolC but not LolE (20), despite their similar structures (37). It therefore seems likely that I93C/F140C binds to the LolC subunit of LolCDE.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation